Radiographic, computed tomographic and arthroscopic diagnosis of the medial coronoid disease - Lau, Seng Fong (Veterinary Association Malaysia, 2014)
Medial coronoid disease (MCD), previously known as ununited or fragmented medial coronoid process (MCP) appears to be the most common component of elbow dysplasia in large breed dogs. Due to the late manifestation of the disease, the pathological findings obtained from clinical patients are usually complicated by degenerative and regenerative changes, with uncertainty whether the findings are causes by or consequences of MCD. And due to the complex articulation of the canine elbow joints, the ideal diagnostic approach for consistently and accurately determining the presence of MCD has yet to be established. Radiography has been used as the first line diagnostic moda lity to diagnose MCD, but most of the time, secondary changes, such as osteophytosis, ulnar subtrochlear sclerosis, and blunting or blurring of the cranial edge of the MCP, have been used to determine the likeliho od of MCD. The use of computed tomography alleviates the problems of superimposition, which improves the examination of the lateral aspect of the MCP. However, both techniques are not allowed the assessment of the articular cartilage and its integrity. On the other hands, arthroscopy serve as both diagnostic and treatment tools and this technique has become more common in veterinary practice. This technique allows more specific, reliable evaluation of MCD lesions within the elbow joint